2012
DOI: 10.1177/1045389x12461081
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-driven self-healing by electrochemical phenomena

Abstract: Self-healing structures mimic the ability of biological structures (e.g. bone) to redistribute their structural mass in response to dynamic service loads and damaging effects. The self-healing features yield enhanced levels of structural efficiency and safety in dynamic service environments. In this study, the piezoelectric effect was used to convert the dynamic mechanical energy applied to the structure into electrical energy that, in turn, was used to drive electrochemical selfhealing phenomena within a soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The adaptive feedback controller was designed and implemented first on a newly developed model of an electrolytic system to regulate the process. The model is based on previous experimental work [6,38] which proposed an electromechanical material system, whose intrinsic self-healing mechanism is based on a piezo-electrolytic drive. This system suffers from an inherent non-linear deadzone which limits the performance of selfhealing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adaptive feedback controller was designed and implemented first on a newly developed model of an electrolytic system to regulate the process. The model is based on previous experimental work [6,38] which proposed an electromechanical material system, whose intrinsic self-healing mechanism is based on a piezo-electrolytic drive. This system suffers from an inherent non-linear deadzone which limits the performance of selfhealing.…”
Section: Resultsmentioning
confidence: 99%
“…This ensures reliability and improved recovery from the effect of damage. To demonstrate the effectiveness of the proposed approach to constant and varying perturbation, an electromechanical material that has previously been experimentally demonstated [6,38] has been modelled and simulated. This paper then shows how adaptive feedback control can compensate for the insufficient potential energy driving the self-healing and can guarantee a response that will match the effect of fault propagation in the simulated system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lang et al 87 demonstrated that HA is both piezoelectric and pyroelectric indicating potential for harvesting human motion and temperature changes; the reader is referred to a review on the topic by Baxter et al 88 A biomimetic approach was used by Soroushian et al who investigated self-healing structures that were able redistribute their structural mass in response to dynamic loads. 89 In their work the piezoelectric effect was used to convert dynamic mechanical energy applied to a structure into electrical energy that was able to drive an electro-chemical self-healing phenomena within a solid electrolyte. Zhang et al also used PVDF to use piezoelectric energy to indirectly power cathodic protection 38 and the output of the fabricated device was used to protect metal surfaces from the chemical corrosion, see Fig.…”
Section: Other Piezo-electro-chemical Applicationsmentioning
confidence: 99%
“…The self‐adaptation capabilities of biological materials such as bone provide the inspiration for development of synthetic materials with inherently adaptive capabilities . Bone uses a powerful control mechanism to reconfigure its structure to remove stress gradients generated after damaging effects for optimum performance.…”
Section: Introductionmentioning
confidence: 99%